Earlier anti-TNF therapy reduces the risk of malnutrition associated with alterations in body composition in patients with Crohn’s disease - Wang, Yuexin; Yao, Danhua; He, Yining; He, Qi; Li, Yousheng (Frontiers in Nutrition, 2023)
Background Anti-TNF therapy has been found to exert an influence on long-term nutritional status and even reverse malnutrition in patients with Crohn’s disease. Aims to observe the effect of anti-TNF therapy on nutritional status in patients with Crohn’s disease, investigate the correlation between the timing of anti-TNF therapy and the human body composition and examine independent body composition factors for predicting malnutrition in these patients. Methods This was a retrospective study of 115 patients with Crohn’s disease. Body composition parameters were assessed by bioelectrical impedance analysis. The nutritional status of the patients was determined by NRS2002 and MNA. Results The BMI, BFMI, FFMI, BCMI, SMI, BMC, intracellular water, protein and BMR were significantly lower in patients without any biologic agents (p < 0.05). Negative correlations were found between BMC, intracellular water, extracellular water, protein and BMR and the interval between the first symptom and first dose by Spearman’s correlation analysis (r < 0, p < 0.05). Low BMI (OR 0.602, 95% CI 0.434–0.836, p = 0.002), low FFMI (OR 0.678, 95% CI 0.507–0.906, p = 0.009), and low BCMI (OR 0.564, 95% CI 0.367–0.868, p = 0.009) were independent risk factors for malnutrition in Crohn’s disease patients. Anti-TNF therapy tended to reduce the malnutrition probability as assessed by Cox regression analysis (OR: 0.217, 95% CI 0.057–0.821, p = 0.024). Conclusion Body composition analysis is predictive of malnutrition in patients with Crohn’s disease. Early application of anti-TNF therapy significantly affected skeletal muscle mass, fat mass and bone mineral content, supporting their long-term nutritional status and reducing their probability of malnutrition.